Deciphering tourism and the acquisition of knowledge: Advancing a new typology of ‘Research-related Tourism (RrT)’ - Shah, Chetan; Trupp, Alexander *; Stephenson, M. L. * (Elsevier, 2022)
‘Research-related Tourism’ (RrT) is broadly defined as any tourism activity in pursuit of learning, exploration or knowledge acquisition. On the basis of this definition, the conceptual paper constructs a RrT typology encapsulating six main types or sub-forms: (1) Scientific Tourism, (2) Education and Academic Tourism, (3) Volunteer Tourism, (4) Business Tourism, (5) Virtual Research Tourism, and (6) Genealogy and Roots Tourism. By conceptualising commonly associated RrT sub-forms (types 1–3), the work situates additional sub-forms (types 4–6) that are not traditionally conceived as conventional types. The enquiry realises that all the types operate synergistically, leading to the formation of RrT categories, attributes and dimensions. The paper's intention is reclarified by enabling and evaluating a robust conception of RrT variations, also establishing a framework for future empirical testing. This enquiry thus enhances the ontological grounding and critical conception of tourism, together with its relationship (and convergence) with research (and knowledge acquisition).